Binding studies of crocin to β-Lactoglobulin and its impacts on both components. (November 2020) - Allahdad, Zahra; Khammari, Anahita; Karami, Leila; Ghasemi, Atiyeh; Sirotkin, Vladimir A.; Haertlé, Thomas; Saboury, Ali Akbar
Abstract: Light susceptibility of crocin and high degree of unsaturation limit its application in food systems. This study aimed to investigate the impact of molecular binding of crocin to β-lactoglobulin (β-LG) on crocin stability as well as the conformational stability of β-LG. The overall binding affinity was estimated about 1.74 × 10 3  M −1 through following UV spectral changes of β-LG at different concentrations of crocin. A 1:1 binding stoichiometry for the complex of crocin and β-LG was recognized using Job's method. The results of molecular docking and molecular dynamic simulation indicated that in addition to a single hydrogen bond with an oxygen linker attached to polyene chain, hydrophobic interactions play the major role in binding of crocin's polyene chain to β-LG surface. Three-dimensional emission and CD spectra showed conformational alterations in both tertiary and secondary structure of β-LG varying with crocin concentration. Depending on the temperature, crocin showed a dual effect on the thermodynamic stability of β-LG. Crocin destabilized β-LG up to room temperature, but stabilized at higher temperatures. The CD spectra of crocin in the Soret region and simulation results proved the bending of polyene chain and changes in the angle between sugar groups and polyene chain in combination with the protein. β-LG complexation enhanced the chemical stability of crocin by 20% during a 30-day storage, while its degradation was accelerated under UV irradiation. According to the results, it is predicted crocin functionalities to be affected by β-LG association and vice versa. Graphical abstract: Image 1 Highlights: The association constant of crocin with β-LG was quantified about 1.74 × 10 3  M −1 . Crocin binding affects β-LG secondary and tertiary structures. Crocin destabilizes β-LG at room temperature, but stabilizes at higher temperatures. β-LG complexation enhances crocin chemical stability during storage. β-LG complexation accelerates crocin degradation under UV irradiation.